At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find all solutions to the equation [tex]\(\cot \theta + \sqrt{3} = 0\)[/tex] within the interval [tex]\([0, 2\pi)\)[/tex], we can follow these steps:
1. Rewrite the equation:
[tex]\[ \cot \theta + \sqrt{3} = 0 \][/tex]
This implies:
[tex]\[ \cot \theta = -\sqrt{3} \][/tex]
2. Express cotangent in terms of tangent:
Recall that [tex]\(\cot \theta = \frac{1}{\tan \theta}\)[/tex]. So, we have:
[tex]\[ \frac{1}{\tan \theta} = -\sqrt{3} \][/tex]
Taking the reciprocal of both sides, we get:
[tex]\[ \tan \theta = -\frac{1}{\sqrt{3}} \][/tex]
We can simplify [tex]\(\tan \theta\)[/tex] further as:
[tex]\[ \tan \theta = -\frac{\sqrt{3}}{3} \][/tex]
3. Determine the reference angle:
We know that [tex]\(\tan \theta = \frac{\sqrt{3}}{3}\)[/tex] for [tex]\(\theta = \frac{\pi}{6}\)[/tex]. Therefore, for [tex]\(\tan \theta = -\frac{\sqrt{3}}{3}\)[/tex], the reference angle is still [tex]\(\frac{\pi}{6}\)[/tex], but the tangent function takes negative values in the second and fourth quadrants.
4. Find the solutions in the specified interval:
- Second Quadrant:
[tex]\[ \theta = \pi - \frac{\pi}{6} = \frac{5\pi}{6} \][/tex]
- Fourth Quadrant:
[tex]\[ \theta = 2\pi - \frac{\pi}{6} = \frac{12\pi}{6} - \frac{1\pi}{6} = \frac{11\pi}{6} \][/tex]
Thus, the solutions to the equation [tex]\(\cot \theta + \sqrt{3} = 0\)[/tex] in the interval [tex]\([0, 2\pi)\)[/tex] are:
[tex]\[ \theta = \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
In decimal form, these are approximately [tex]\(2.6179938779914944\)[/tex] and [tex]\(5.759586531581287\)[/tex], respectively, which confirms our earlier findings.
So, the final answer is:
[tex]\[ \theta = \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
1. Rewrite the equation:
[tex]\[ \cot \theta + \sqrt{3} = 0 \][/tex]
This implies:
[tex]\[ \cot \theta = -\sqrt{3} \][/tex]
2. Express cotangent in terms of tangent:
Recall that [tex]\(\cot \theta = \frac{1}{\tan \theta}\)[/tex]. So, we have:
[tex]\[ \frac{1}{\tan \theta} = -\sqrt{3} \][/tex]
Taking the reciprocal of both sides, we get:
[tex]\[ \tan \theta = -\frac{1}{\sqrt{3}} \][/tex]
We can simplify [tex]\(\tan \theta\)[/tex] further as:
[tex]\[ \tan \theta = -\frac{\sqrt{3}}{3} \][/tex]
3. Determine the reference angle:
We know that [tex]\(\tan \theta = \frac{\sqrt{3}}{3}\)[/tex] for [tex]\(\theta = \frac{\pi}{6}\)[/tex]. Therefore, for [tex]\(\tan \theta = -\frac{\sqrt{3}}{3}\)[/tex], the reference angle is still [tex]\(\frac{\pi}{6}\)[/tex], but the tangent function takes negative values in the second and fourth quadrants.
4. Find the solutions in the specified interval:
- Second Quadrant:
[tex]\[ \theta = \pi - \frac{\pi}{6} = \frac{5\pi}{6} \][/tex]
- Fourth Quadrant:
[tex]\[ \theta = 2\pi - \frac{\pi}{6} = \frac{12\pi}{6} - \frac{1\pi}{6} = \frac{11\pi}{6} \][/tex]
Thus, the solutions to the equation [tex]\(\cot \theta + \sqrt{3} = 0\)[/tex] in the interval [tex]\([0, 2\pi)\)[/tex] are:
[tex]\[ \theta = \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
In decimal form, these are approximately [tex]\(2.6179938779914944\)[/tex] and [tex]\(5.759586531581287\)[/tex], respectively, which confirms our earlier findings.
So, the final answer is:
[tex]\[ \theta = \frac{5\pi}{6}, \frac{11\pi}{6} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.